Applications of Paddle Wheel Aerators and Diffused-Air System in Closed Cycle Shrimp Farm System - Wara Taparhudee (Agriculture and Natural Resources, 2002)
Shrimp culture practices are changing from high water exchange systems to low water exchange systems to reduce the risk of disease contamination and water pollution. The low water exchange systems require a great number of aerators to prevent water deterioration due to high organic loading associated with limited water exchange. However, high rates of aeration can not only cause excessive water currents and erode pond bottom badly but also increase power cost. In this present study, applications of paddle wheel aerators and diffused-air systems were investigated in grow-out ponds of a closed cycle farm. The results showed that these systems were successful used in shrimp production, and of the systems examined, a combination of paddle wheel and medium bubble size diffused-air system, with a polyethylene pipe network proved to be most effective and convenient. This aeration system provided suitable dissolved oxygen concentrations to the water body and the pond bottom, which could stimulate decomposition at the pond bottom. In addition, this system had low operating costs. It is suitable to be applied in low water exchange culture systems and it can also reduce problems of pond bottom erosion, a typical problem, when using large numbers of paddlewheels.